Analisis Laporan Keuangan Subsektor Material Konstruksi yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Arini, Arini; Amorine, Sheryl (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2024)
Companies whose capital is divided into shares must submit financial reports every certain period of time. The financial statements are very useful for stakeholders as a consideration before making decisions. To be able to provide maximum benefits, financial reports need to be analyzed. The financial statements to be analyzed in this study are the cement industry in construction material subsector for the period 2018-2022. The subsector was chosen because cement is the main raw material for infrastructure development in Indonesia which still quite potential to increase revenue for cement companies. The purpose of this study is to provide information to stakeholders regarding the financial performance of the construction material subsector as seen from the level of liquidity, solvency, profitability, and activity during the period 2018-2022. The research method used in this research is library research method and data analysis using financial ratios. The research was conducted on 4 (four) companies included in the construction material subsector on the Indonesia Stock Exchange. The analysis results show that PT Indocement Tunggal Prakarsa Tbk (INTP) has the best liquidity, solvency, profitability, and activity ratios compared to similar companies during the period 2018-2022.